Optimizing EFL Learning: Digital Native Leverage Mobile-Assisted Language Learning (MALL) - Siti Saridah; Dedi Sulaeman; Pepi Siti Faturohmah; Ruminda Ruminda (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2024)
This study intends to explore the leverage of technology devices and their impact on the digital natives’ experiences in enhancing EFL learning using Mobile-Assested Language Learning (MALL). Pointedly, (1) how digital natives’ attitudes toward technology influence their use of smartphones for EFL learning, and (2) the effectiveness of MALL activities in boosting English skills.  Then, this research uses a narrative inquiry research design with in-depth interviews of six English teachers in various grades. By using thematic analysis revealed that digital natives enjoy the interactive nature of MALL activities and concern arose regarding their potential dependence on personal devices. The findings have been obtained to answer the questions that have been desired. (1) digital natives look to enjoy with MALL procedures; it narrates with digital natives’ interest and, (2) Mobile-Assisted Language Learning (MALL) offers digital natives particularly to access web-based learning and online learning courses. These provide audio-visual presentations that are helpful for digital natives to supercharge their English competencies with various activities. These findings ensure that Mobile-Assisted Language Learning (MALL) is a valuable potential tool in EFL classrooms, but careful attention to consideration for fostering responsible technology use in addressing potential distractions.